A fast HRMA tool to authenticate eight salmonid species in commercial food products. (October 2021) - Monteiro, Carolina Sousa; Deconinck, Dumas; Eljasik, Piotr; Sobczak, Małgorzata; Derycke, Sofie; Panicz, Remigiusz; Kane, Nicola; Mazloomrezaei, Mohsen; H. Devlin, Robert; Faria, Miguel A.
Abstract: Atlantic and Pacific salmon are frequently consumed species with very different economic values: farmed Atlantic salmon is cheaper than wild-caught Pacific salmons. Species replacements occur with the high valued Pacific species ( Oncorhynchus keta, O. gorbuscha, O. kisutch, O. nerka and O. tshawytscha ) substituted by cheaper farmed Atlantic salmon ( Salmo salar ) and Atlantic salmon by rainbow trout ( Oncorhynchus mykiss ) and brown trout ( Salmo trutta ). Here we use High-Resolution Melting Analysis (HRMA) to identify eight salmonid species. We designed primers to generate short amplicons of 72 and 116 bp from the fish barcode genes CO1 and CYTB. The time of analysis was under 70 min, after DNA extraction. Food processing of Atlantic salmon (fresh, "Bellevue", "gravadlax", frozen and smoked) did not impact the HRMA profiles allowing reliable identification. A blind test was conducted by three different institutes, showing correct species identifications irrespective of the laboratory conducting the analysis. Finally, a total of 82 retail samples from three European countries were analyzed and a low substitution rate of 1.2% was found. The developed tool provides a quick way to investigate salmon fraud and contributes to safeguard consumers.